‘Blood as the Seat of Life’: The Blood Paradox among Afro-Christians - Machingura, Francis (Perichoresis, 2016)
The study is a response to the call for papers on African issues and it focuses on the theme of blood. The chapter seeks to answer the following questions: Why is blood, the sanctity of life, associated with defilement? How can the good and purity of life which blood symbolizes come out of impurities? How is the practice of blood manipulation represented in biblical texts? How can bodily refuse in this case blood be conceived as a symbol of purity, power and danger? How do readers of biblical texts understand the textual representations and interpretations of blood? Does each mode of blood manipulation rituals function as communicative symbols? Our response to these questions is threefold. First, we consider the sanctity of blood in relation to its purity and power. This is followed by an examination of danger beliefs associated with blood and lastly by an analysis of the sacred/taboo or purity/danger dichotomy within the context of the Old Testament and the New Testament as well as of the Shona Afro-Christians.